Magnesium-Rich Nanometric Layer in the Skeleton of Pocillopora damicornis With Possible Involvement in Fibrous Aragonite Deposition - Shapiro, Orr H.; Kartvelishvily, Elena; Kramarsky-Winter, Esti; Vardi, Assaf (Frontiers in Marine Science, 2018)
The complex structures and morphologies of coral skeletons make it difficult to study the construction of individual skeleton components. This is especially true regarding micro-structures deposited during different stages of skeletogenesis. As such structures serve as the basis for subsequent skeleton development, they are often obscured by additional skeletal deposition and growth. Recently we described a new model system, coral-on-a-chip, for studying coral biology and skeletogenesis. This system utilizes micropropagates of the Indo-Pacific coral Pocillopora damicornis maintained within a microfluidic environment, allowing us to follow early stages of skeletogenesis over time and under controlled environmental conditions. Our findings reveal that, following settlement onto glass slides, the micropropagates initially form a thin, almost two dimensional skeleton, which subsequently develops into a robust three-dimensional form with features resembling those of the mother colony. Studying the early stages of skeleton accretion in our micropropagates using high-resolution scanning electron microscopy and Energy Dispersive X-ray Spectroscopy (EDS) revealed a magnesium-rich layer deposited directly on the glass surface. This layer, which has a typical Mg/Ca ratio of 1.43±0.78, forms a dense lattice with a typical pore size of 100 nm. Microscopic observations indicate that this lattice serves as the basis for subsequent growth of fibrous aragonite. Examination of the underside of a skeleton from a small P. damicornis colony growing on a glass surface revealed a similar high-magnesium lattice at the interface between the glass and aragonitic skeleton in association with fibrous aragonite deposition. These observations suggest a role for this magnesium-rich lattice in the deposition of the fibrous aragonite forming the bulk of the coral skeleton.